Transmission Electron Mmicroscopy of In Vitro Biofilms formed by Candida albicans and Escherichia coli - Suba, Sally C.; Masangkay, Frederick R. (Asian Journal of Biological and Life Sciences, 2013)
To evaluate in vitro interactions of Escherichia coli and C. albicans in pure and dual-species biofilm, and to assess biofilm formation. Clinical isolates were grown in thioglycollate broth. Sessile cells were cultured in Blood agar plate (BAP) and grown on copper grids for Transmission Electron Microscopy (TEM) negative staining. Sessile cells were also grown in Eppendorf tubes with thioglycollate, preserved ultra-thin sections of which were processed for positive staining. C. albicans in pure and co-culture with E. coli in thioglycollate exhibited blastospore morphotypes only. Biofilm towers predominated in C. albicans pure culture and demonstrated “blob” formations. Networking architecture was observed in pure colonies of E. coli. In vitro co-cultures demonstrated down-regulated biofilm formation, decreased cellularity and degraded yeast cells. Biofilm phenotypes were present in both bacterial and fungal sessile cells from the urine sample and pose as obstacles in effective drug therapy. Therefore it is necessary that methodologies for effective isolation of sessile cells be employed for the judicious application and management of drug susceptibility testing directed towards sessile cells in vitro as baseline for antimicrobial therapy in vivo.